2021
DOI: 10.1080/14760584.2021.1938550
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 pandemic: SARS-CoV-2 specific vaccines and challenges, protection via BCG trained immunity, and clinical trials

Abstract: Introduction : The coronavirus disease 2019 (COVID-19) pandemic continues to spread worldwide and vaccination remains the most effective approach to control COVID-19. Currently, at least ten COVID-19 vaccines have been authorized under emergency authorization. However, these vaccines still face many challenges. Areas covered : This study reviews the concept and mechanisms of trained immunity induced by the Bacille Calmette Guérin (BCG) vaccine and identifies questions that sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 95 publications
(118 reference statements)
0
30
0
Order By: Relevance
“…Although there is scant information on how the BCG vaccine could modify the development of infection from SARS-CoV-2, the number of reports is increasing rapidly [21]; however, some are controversial [22] and most of these studies propose training the immune system for subsequent contact with the novel coronavirus [23]. However, most of these hypotheses are based on statistical relationships in which it is intended to evaluate the history of vaccination in childhood, and parameters such as morbidity and mortality due to COVID-19 [24].…”
Section: Discussionmentioning
confidence: 99%
“…Although there is scant information on how the BCG vaccine could modify the development of infection from SARS-CoV-2, the number of reports is increasing rapidly [21]; however, some are controversial [22] and most of these studies propose training the immune system for subsequent contact with the novel coronavirus [23]. However, most of these hypotheses are based on statistical relationships in which it is intended to evaluate the history of vaccination in childhood, and parameters such as morbidity and mortality due to COVID-19 [24].…”
Section: Discussionmentioning
confidence: 99%
“…Vaccination is the most effective way to control TB. The only licensed TB vaccine is Bacille Calmette-Guérin (BCG), which has been used for more than 100 years ( 6 , 7 ). Previous studies have reported that BCG can protect children from severe TB and miliary TB.…”
Section: Introductionmentioning
confidence: 99%
“…A worldwide race to develop a vaccine against SARS-CoV2 started after the emergence of the COVID-19 pandemic [14]. Up to now, at least ten COVID-19 vaccines were emergency authorized [15] with the hope of ending the pandemic via herd immunity [14,16]. The worldwide vaccine skepticism and hesitancy are the main obstacles to rapidly reaching herd immunity [17][18][19].…”
Section: Introductionmentioning
confidence: 99%